2006
DOI: 10.1080/09243450600565746
|View full text |Cite
|
Sign up to set email alerts
|

Transformational and transactional leadership effects on teachers' job satisfaction, organizational commitment, and organizational citizenship behavior in primary schools: The Tanzanian case

Abstract: This article may be used for research, teaching, and private study purposes. Any substantial or systematic reproduction, redistribution, reselling, loan, sub-licensing, systematic supply, or distribution in any form to anyone is expressly forbidden.The publisher does not give any warranty express or implied or make any representation that the contents will be complete or accurate or up to date. The accuracy of any instructions, formulae, and drug doses should be independently verified with primary sources. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

61
396
6
32

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 467 publications
(533 citation statements)
references
References 68 publications
61
396
6
32
Order By: Relevance
“…Organizational citizenship is one of the few individual variables that influence organizational effectiveness (Bogler and Somech, 2004;Nguni et al, 2006;Oplatka, 2006;Organ, 1988;1997;Paine and Organ, 2000;Podsakoff et al, 1990;Podsakoff et al, 1996, Podsakoff et al, 2000Somech and Drach-Zahavy, 2004). The concept of OCB draws primarily upon Chester Barnard's concept of 'willingness to change' and Daniel Katz's notion of 'distinction between dependable role and performance' and 'innovative and spontaneous behaviors' (Podsakoff et al, 2000, p. 513).…”
Section: Organizational Citizenship Behaviorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Organizational citizenship is one of the few individual variables that influence organizational effectiveness (Bogler and Somech, 2004;Nguni et al, 2006;Oplatka, 2006;Organ, 1988;1997;Paine and Organ, 2000;Podsakoff et al, 1990;Podsakoff et al, 1996, Podsakoff et al, 2000Somech and Drach-Zahavy, 2004). The concept of OCB draws primarily upon Chester Barnard's concept of 'willingness to change' and Daniel Katz's notion of 'distinction between dependable role and performance' and 'innovative and spontaneous behaviors' (Podsakoff et al, 2000, p. 513).…”
Section: Organizational Citizenship Behaviorsmentioning
confidence: 99%
“…In this regard, OCB is one of the constructs that has continued to interest scholars, practitioners, and policy-makers to influence school effectiveness and improvement (Feather and Rauter, 2004;Nguni et al, 2006;Oplatka, 2006;Organ, 1988Organ, , 1997Ölçüm-Çetin, 2004;Paine and Organ, 2000;Podsakoff et al, 2000;Sezgin, 2005). Teacher OCBs are crucial for schools as the construct relates to non-formally prescribed behaviors including teachers' exerting extra effort and time and taking the responsibility of school improvement individually (Hoy et al, 1991;Somech and Ron, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has found that transformational leadership has a large effect on organizational commitment (Dee, Henkin, & Singleton, 2004;Koh et al, 1995;Nguni, Sleegers, & Denessen, 2004). Transformational leadership is also a contributor to a closely related concept, organizational citizenship (Koh et al, 1995;Leithwood, Tomlinson, & Genge, 1996;Nguni et al, 2004;Podsakoff et al, 1990) that refers to an individual's willingness to go beyond the formal requirements of the job to engage in productive functions that enhance organizational effectiveness.…”
Section: Theoretical Framework Relationship 1: the Effects Of Leadersmentioning
confidence: 99%
“…Several studies supported the effect of principal's leadership behaviours on teachers' job satisfaction (Dinham & Scott, 1998;Bogler, 2001;Griffith, 2004;Nguni et al, 2006;Cerit, 2009). Studies proved that the principal's leadership behaviour is one of the positive factors that have a direct correlation with teachers' job satisfaction (Bogler, 2001).…”
Section: Principal Leadership Behaviour and Teacher Job Satisfactionmentioning
confidence: 88%